When Mucolipidosis III meets Mucolipidosis II: GNPTA gene mutations in 24 patients - ELÇİOĞLU, HURİYE NURSEL (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2006)
Mucolipidosis II (ML II) and Mucolipidosis type III (ML III) are autosomal recessive disorders of lysosomal hydrolases trafficking due to the deficiency of the multimeric enzyme, UDP-N-acetylglucosamine-l-phosphotransferase. The alpha/beta subunits encoded by the GNPTA gene is the catalytic subunit of the enzyme while the gamma recognition subunit is encoded by the GNPTAG gene. We report the molecular analysis of GNPTA in 21 families with ML IT and 3 families with ML III. The ML II mutant genotypes included three splice-site mutations [TVs] -2A > G; IVS17 + IG > A; IVSI 8 + IG > A] in seven Palestinian, Israeli Arab-Muslims, and Turkish patients; a two base pair deletion [c.3502_3delCT] in I I patients from Israel, Turkey, and Ireland; two nonsense mutations [c.2533C > T (Q845X); c.3613C > T (R 1205X)], in a Turkish and an Arab-Muslim patient from the Nablus area, respectively, and an insertion mutation [c.2916insT] in a patient from Nablus. The ML III mutant genotypes included a splice-site mutation [IVS17 + 6T > G] in two patients from Irish/Scottish origin who were compound heterozygous for a nonsense mutation fe.3565C > T (R1189X)] and the deletion mutation [c.3502_3delCT], respectively. The third ML III patient from France was compound heterozygous for a missense mutation [c.1196C > T] and the same deletion [c.3502_3delCT] found homozygous in I I ML II patients. The 21 ML II patients were homozygous while the three ML III patients were compound heterozygous for mutations in GNPTA. The results of this study confirm that ML II or ML III phenotype is not due to the localization of the mutations, but rather to the severity of the mutations, ML II and ML III might be allelic, and ML III is genetically heterogeneous. We suggest that the diseases due to mutations in GNPTA represent a clinical continuum between ML III and ML II, and the classification of these diseases should be based on the age of onset, clinical symptoms, and severity. C 2006 Elsevier Inc. All rights reserved.
Keywords: Mucolipidosis II; Mucolipidosis III; GNPTA; GNPTAG; PSEUDO-HURLER POLYDYSTROPHY; PHOSPHOTRANSFERASE ALPHA/BETA-SUBUNITS; UDP-N-ACETYLGLUCOSAMINE; CELL DISEASE; N-ACETYLGLUCOSAMINE-1-PHOSPHOTRANSFERASE; GLCNAC-1-PHOSPHOTRANSFERASE; IDENTIFICATION; ENZYME